BUILD RELIGIOUS CHARACTER THROUGH 5S (SENYUM, SAPA, SALAM, SOPAN, SANTUN) - Nita Eka Rahmawati; Ngaenu Rofiqoh; Lutfia Islahati; Moh Salimi (Universitas Sebelas Maret, 2018)
Character building programs are being promoted at school. So that schools need to plan programs to support these character education program, one of which is through the 5S program. The purpose of this study is 1) to describe about 5S program, 2) describe the character developed by 5S. The results of this study are 1) 5S (Senyum, Sapa, Salam, Sopan, Santun) is a program that is implemented to develop character through habituation in the school environment by school residents, 2) the character developed through the 5S program is a religious character in which there is a value of love for peace, friendship, ethics.